CHARACTERISTICS OF SKILLS AND SKILLS OF SELF-CONTROL AND STAGES OF THEIR FORMATION IN STUDENTS IN THE PROCESS TEACHING (Pedagogy of Higher and Secondary Education, 2008)
In the article author analyses the notion of abilities and skills of self-control, defines the stages of its forming at the pupils in the process of their educational-cognitive activity.